Studies in Health Technology and Informatics Volume 25 - Education and Training in Health Informatics in Europe - Hasman, A. (IOS Press, 2014)
In 1990, the Committee of Ministers of the Council of Europe issued a recommendation (Recommendation No. R(90)21) to the governments of member states to ensure that all professionals involved in healthcare receive as soon as possible appropriate education and training in health informatics. The EDUCTRA (Education and Training in Health Informatics) Concerted Action, established in 1992 under the auspices of the AIM (Advanced Informatics in Medicine) European programme, and consisting of representatives of all member states, conducted a Europeanwide survey. This survey showed that the above Recommendation had received little attention in most member states. It also revealed considerable gaps (i) in the knowledge of healthcare professionals with respect to the basic principles of health informatics, and (ii) in the adequate use of modern information technology.